Geographical Distribution and Long-Term Monitoring of Physokermes hellenicus (Hemiptera: Coccomorpha: Coccidae) on Abies spp. (Pinales: Pinaceae) in Greece - Iosif Papanastasiou (MDPI AG, 2021)
The scale Physokermes hellenicus (Kozár & Gounari) (Hemiptera: Coccidae) has been recently included in the Greek entomofauna as a beneficial honeydew species. However, there are no adequate data about its geographical distribution and degree of infestation. Therefore, a study was conducted to examine these parameters in fifteen mountains of Greece. Furthermore, the monitoring of P. hellenicus infestation was carried out over a six-year period with regard to natural enemies and honeydew presence at three mountains (i.e., Menalon, Parnis and Tymfristos) that are traditional honeybee foraging areas. An extensive geographical distribution of the scale was negatively correlated with the latitude. Over the period of the study, P. hellenicus infestation exhibited a decreasing trend in the three mountains, which was more obvious at Menalon. The abundance of natural enemies of P. hellenicus, their effectiveness on honeydew excretion and the fecundity of P. hellenicus are discussed. The reduction in the honey produced at the Menalon mountain (a protected designation of origin product) could be attributed to the reduced presence of P. hellenicus in the fir forest. Among the other identified arthropods, Dreyfusia nordmannianae Eckstein (Hemiptera: Adelgidae) is reported for the first time infesting Abies cephalonica (Pinales: Pinaceae) in Greece. Furthermore, this species is reported for the first time as a co-parasite with P. hellenicus on A. cephalonica in Greece. Since D. nordmannianae is a serious pest, additional research is needed to determine its status in Greek fir forest ecosystems.